Absolute Quantification Method for Protein Concentration - Li, Mingdong; Tan, Jiaojie; Tarlov, Michael J; Zachariah, Michael R (Analytical chemistry (Washington), 2014)
A fast and accurate assay to determine the absolute concentration of proteins is described based on direct measurement of droplet entrapped oligomer formation in electrospray. Here we demonstrate the approach using electrospray differential mobility analysis (ES-DMA), which can distinguish monomers and dimers from higher order oligomers. A key feature of the method is that it allows determination of the absolute number concentration of proteins eliminating the need for protein-specific calibration. The method was demonstrated by measuring the concentration of a NIST Standard Reference Material 927e (bovine serum albumin), a high-purity immunoglobulin G 1κ, and a formulated Rituximab. The method may be applied to any electrospray source, regardless of diagnostic tool (e.g., MS or ion-mobility, etc.), provided the electrospray is operated in a droplet-fission mode.